Política educativa en el Perú en la transición del siglo XX al siglo XXI: del trabajo como principio educativo al emprendedorismo en la educación - Juan Arturo Maguiña Agüero (2019)
The research proposed as a problem the study of educational ideas manifested in contemporary Peru, in the transition from the 20th to the 21st century. Our research problema is expressed in the question: What were the approaches of educational policy and hegemonic and subordinate ideologies in Peru during the transition from the 20th to the 21st century regarding the purposes of education in relation to the job? The years of 1990 and 2000 correspond to the beginning and end of the authoritarian regime of President Alberto Fujimori. This period was selected because it corresponds to the years in which the implementation of the educational policy called “Educational Modernization” occurred (19922000) and which consisted of the implementation of the neoliberal educational model prescribed by the World Bank and various supranational organizations. The theoretical references of this research are Karl Marx and Antonio Gramsci. From these thinkers we take and problematize their conceptions of culture, intellectuality and education in relation to work as a fundamental human expression. We consider pertinent the ideas of these thinkers, since they had a critical vision of the established hegemonic order, which still maintains its validity to understand the world of today. Their analysis, even when it had an ideological basis and political objectives, was not without philosophical and scientific consistency. From Marx we take the thesis of work as an activity by which man transforms what exists to satisfy his physical needs and build his spiritual world. From Gramsci we take the confirmation of the role of the intellectuals as non-autonomous organic officials and dependent on the social groups whose interests they represent. Our objective, starting from the Marxist and Gramscian postulates, is to show the interrelationships between the plane of the ideological postulates and the intellectual production as elements of construction and maintenance of the Peruvian educational policy in the indicated period. This research contributes to increasing knowledge in the area of the history of educational ideas in Peru and in the area of design and implementation of public policies in Peruvian education.